A red light-controlled probiotic bio-system for in-situ gut-brain axis regulation. (March 2023) - Zhang, Xinyu; Pang, Gaoju; Sun, Tao; Liu, Xinyu; Pan, Huizhuo; Zhang, Yingying; Liu, Jing; Chang, Jin; Wang, Hanjie; Liu, Duo
Abstract: Microbes regulate brain function through the gut-brain axis, deriving the technology to modulate the gut-brain axis in situ by engineered probiotics. Optogenetics offers precise and flexible strategies for controlling the functions of probiotics in situ . However, the poor penetration of most frequently used short wavelength light has limited the application of optogenetic probiotics in the gut. Herein, a red-light optogenetic gut probiotic was applied for drug production and delivery and regulation of the host behaviors. Firstly, a Red-light Optogenetic E. coli Nissle 1917 strain (ROEN) that could respond to red light and release drug product by light-controlled lysis was constructed. The remaining optical power of red light after 3 cm tissue was still able to initiate gene expression of ROEN and produce about approximately 3-fold induction efficiency. To give full play to the in vivo potential of ROEN, its responsive ability of the penetrated red light was tested, and its encapsulation was realized by PH-sensitive alginate microcapsules for further oral administration. The function of ROEN for gut-brain regulation was realized by releasing Exendin-4 fused with anti-neonatal Fc receptor affibody. Neuroprotection and behavioral regulation effects were evaluated in the Parkinson's disease mouse model, after orally administration of ROEN delivering Exendin-4 under optogenetic control in the murine gut. The red-light optogenetic probiotic might be a perspective platform for in situ drug delivery and gut-brain axis regulation.